National identity: Prediction model of relationship between language decency and language character - Abdul Rasid Jamian; Rosmaria Omar; Mohd Rashid Md Idris; Azhar Wahid; Ariff Mohamad; Norfaizah Abdul Jobar; Khairil Ansary (International Journal of Evaluation and Research in Education (IJERE), 2022)
The expression of decency in communication triggers individual character in formation of national identity. Language decency always applies in Malay language education context during learning session. But, how far it can shape the generation’s identity is still vague. Aim of this research was to thorough the relationship of language education decency with language character among students in public and private universities. A survey was conducted on 380 students of several universities in Malaysia. The data were collected by using Google Form with cooperation from university representatives. The quantitative data was analyzed by using SPSS and AMOS software through correlation and regression analysis by structural equation modelling (SEM). Findings showed that the most decency form used by students was words with value β=.67, p=.000. Language decency education had contributed 80% of R2 value for language character among students. The prediction model of relationship between decency language and character language had achieved equivalence value which RMSEA=.067, GFI=.977, CFI=.995, TLI=.991 and Chisq/df=2.682. Therefore, factor of decency language that applies among students in Malay language course can contribute on generation with nice language character and strong national identity.